The worlds of the trust / edited by Lionel Smith. - Smith, Lionel D. (Cambridge University Press, 2013)
Despite the common belief that they are found only in the common law tradition, trusts have long been known in mixed jurisdictions even where they have a civilian law of property. Trusts have now been introduced by legislation in a number of civilian jurisdictions, such as France and China. Other recent developments include the reception of foreign trusts through private international law in Italy and Switzerland and the inclusion of a chapter on trusts in Europe's Draft Common Frame of Reference. As a result, there is a growing interest in the ways in which the trust can be accommodated in civil law systems. This collection explores this question, as well as general issues such as the juridical nature of the trust, the role and qualifications of the trustee and particular developments in specific jurisdictions.